Metal‐Organic Framework Sandwiching Porous Super‐Engineering Polymeric Membranes as Anionphilic Separators for Dendrite‐free Lithium Metal Batteries. (14th September 2022) - Lin, Guo; Jia, Kun; Bai, Zhongxiang; Liu, Chenchen; Liu, Shuning; Huang, Yumin; Liu, Xiaobo
Abstract: The development of multifunctional separators can be an effective solution for solving the lithium dendrite and safety issues of lithium metal batteries (LMBs). This study reveals an interfacial reaction protocol to prepare a functional separator to regulate lithium‐ion transport and enhance the safety of LMBs. Specifically, the well‐organized anionphilic MOFs layers are in situ grafted on both sides of porous super‐engineering polyarylene ether nitrile (PEN) membranes pre‐modified with polydopamine (PDA), which leads to sandwiched MOF/PEN@PDA/MOF multifunctional separators. Electrochemical tests prove that the optimized separator acts as a "Li‐ion guides" to balance the internal electric field and limit the free migration of anions, which extends the "Sand's time" of lithium dendrite nucleation and contributes a high Li + transfer number of 0.81. On account of the alleviated interface side reactions, the optimized battery exhibits a highly stable lithium plating–stripping cycle of over 500 h. Meanwhile, the functional separator shows better thermal stability than its conventional polypropylene counterpart. Thanks to these features, the assembled LFP/Li cells with optimized separator exhibit stable cycling performance and high coulombic efficiency of 98% even at 90 °C. The current study opens a new path to designing separators for solving the lithium dendrite and safety issues of LMBs. Abstract : Based on the interfacial design and dual‐solvent‐induced synthesis strategy, a uniform, interlocked, and phase‐pure MOFs layer with anionphilic features is built on the two sides of porous super‐engineering polymeric membranes for a lithium metal battery separator. MOFs layer‐faced electrodes can act as a "Li‐ion guides" to balance the internal electric field and limit the free migration of anions, contributing to a stable lithium plating–stripping metal interface. The non‐shrinkage hybrid separator with a microporous structure also prevents resultant lithium‐metal batteries from internal short circuits, chemical crosstalk of reactive gases, as well as the associated exothermic reactions.